Energy–efficient power allocation algorithms for mobile wireless sensor networks. (27th January 2015) - Tolba, Fatiha Djemili; Magoni, Damien; Lorenz, Pascal; Ajib, Wessam
This paper proposes new distributed algorithms of adaptive transmit power allocation in wireless sensor networks for improving the efficiency of energy management. The proposed algorithms are based on two fundamental criteria namely: the distance between the sensor and the sink, and the distance between the sensor and its two–hop neighbours. Each sensor can manage its own transmission power according to these two criteria in order to reduce its energy consumption. The proposed algorithms help both extending the network lifetime and reducing the work load of sensors that are located close to the base station. The used sensors are subject to premature battery exhaustion since they relay the traffic of other sensors toward the sink. We also consider the coverage constraint requiring that all regions must be always covered. This coverage constraint justifies the choice of the two–hop neighbours criterion. Extensive simulation results show the benefits obtained by the proposed algorithms on various important metrics.